Incorporating maintenance and upgrade of buildings in the revision of the National Building Code of the Philippines - Urrea, Jeshaiah N.
The National Building Code of the Philippines (NBCP), also known as Presidential Decree 1096, contains the minimum requirements in building construction. Since its development in 1977, there were no revisions made regarding this decree despite the current technological advancemems and engineering improvements being known globally. This problem was further strengthened by the recent disasters that hit the country which caused major damages to buildings such as the Magnitude 7.2 Bohol Earthquake and the Category 5 Typhoon Yolanda (Haiyan). In connection to this, maintenance and upgrade is one of the building code elements which was not fully addressed in this code. With this, this study aimed to compare the National Building Code of the Philippines with the building codes of several countries including the United States of America, Japan, India, Indonesia and New Zealand, further focusing on the aspect regarding maintenance and upgrade. After identifying the universally accepted building code clements extracted from several internationally recognized groups and studies, the building codes of the said countries were mapped with respect to the derived list of elements. The elements were then classified into six levels depending on the extensiveness of their provisions. It was found out that in the Philippines, maintenance and upgrade was indeed one of the elements with the least extensive requirements. Gaps in this area were determined and recommendations addressing these were provided by this study.